A study of efficiency in the Vietnamese banking sector - Nguyen, Ha Thu (2009)
This paper investigates whether in Vietnam the state – owned commercial banks (SOCBs) are more or less efficient than the joint stock commercial banks (JSBs), and whether large commercial banks are more or less efficient than small commercial banks. Employing the stochastic cost frontier approach, scale – efficiency and X – efficiency scores are estimated for thirty-four Vietnamese commercial banks over the period of four years from 2005 – 2008. Overall, the results suggest that state – owned commercial banks are not as efficient as the joint stock commercial banks in term of both scale and X – efficiency. In addition, the data shows that banks with medium asset size (50,000 – 100,000 billions VND for JSCs and 200,000 billions VND for SOCBs) have highest efficiency scores, compared to both small banks and large banks.